Mapping focus to prosody in Italian - Giuliano Bocci; Valentina Bianchi; Silvio Cruschina (Isogloss)
Italian wh-questions with bare wh-elements are characterized by an exceptional prosodic pattern, whereby the nuclear pitch accent (NPA) is assigned neither to the wh-element nor to the default rightmost position, but it rather falls on the lexical verb, even though this is not semantically interpreted as a focus. Based on evidence from production, in previous work we argue that the NPA assignment is a reflex of the cyclic syntactic derivation, being sensitive to a syntactic [focus] feature borne by the wh-phrase. The striking dissociation between the NPA and focal interpretation that emerges from the production data raises the question of whether Italian hearers are sensitive to this marked prosodic pattern in understanding a question. To address this question, we carried out a comprehension experiment, where we manipulated the position of the NPA in biclausal wh-questions including two verbs: the verb of the matrix clause and the embedded verb. The results of this experiment confirm the psychological reality of our theoretical analysis, suggesting that hearers exploit prosodic cues to parse the sentence and to assign the correct interpretation to structures that only differ at the surface level with respect to the position of the NPA.